Relationship between Healthy Home Score and Stunting Degree in Toddlers in The Work Area of Lok Bahu Community Health Center: Hubungan Skor Rumah Sehat dengan Derajat Stunting pada Balita di Wilayah Kerja Puskesmas Lok Bahu - Pahlevi, Muhammad Reza; Akbar, Khairul; Fadilla, Shella; Harianja, Gabriella Bioctin Harianja; Sudrajat, Aulia Aisyah; Damin, Dini Angelina Putri; Nabilah, Nur Fauziah; Fitriany, Evi; Noor, Zulhijrian (Jurnal Riseta Naturafarm, 2025)
Stunting is a condition where children under five years old have a nutritional status based on their height or length-for-age z-score less than -2SD, categorized as stunted, and categorized as severely stunted if the z-score is below -3SD. Many factors can affect the severity of stunting, not only internal factors but also external ones. Environmental conditions, including the home environment, can influence stunting, which can be assessed through a healthy home score. The aim of this study is to determine the relationship between the healthy home score and its impact on the degree of stunting in children. This analytical observational study with a cross-sectional approach used data from 42 stunted children from all Posyandu in Lok Bahu during the measurement period in June 2024. Statistical analysis used the Spearman correlation test, and if the p-value is <0.05, a significant correlation was found. The results showed that there were 27 boys and 15 girls. Children aged 12 to 23 months dominated, accounting for 12 out of 42 children. The relationship between the resident behavior score and the degree of stunting showed a p-value of 0.01 and r = 0.36. It was concluded that, only resident behavior had a significant relationship with the degree of stunting with positive correlation.